Performance analysis of a thermoelectric cooler with a corrugated architecture. (1st June 2015) - Owoyele, Opeoluwa; Ferguson, Scott; O'Connor, Brendan T.
Highlights: We model a unique hybrid thermoelectric architecture with a corrugated structure. COP of the corrugated TE similar to conventional "bulk" TE module. Cooling power density of corrugated TE shown to be much lower than a bulk TE. Heat transfer coefficient of the corrugated TE lower than bulk TE for typical applications. Corrugated TE shown to have potential fabrication and implementation benefits. Abstract: A thermoelectric (TE) cooler architecture is presented that employs thin film thermoelectric elements on a plastic substrate in a corrugated structure sandwiched between planar thermal interface plates. This design represents a hybrid of a conventional bulk TE device and an in-plane thin film TE design. This design is attractive as it may benefit from low cost thin-film processing in a roll-to-roll fashion onto low-cost plastics substrates while maintaining a cross-plane heat flux for large area applications and a geometry that assists in maintaining a significant temperature difference across the thermoelectric elements. First, the performance of a single thermocouple is analyzed and the effect of the parasitic heat loss through the plastic substrate is examined. The performance of an array of thermocouples is then considered and the effects of various geometric parameters are analyzed with particular focus on the packing density of thermoelectric legs. The results show that while the coefficient of performance ( COP ) is comparable to a conventional bulk element TE cooler, the cooling power density drops off dramatically with a decrease in stacking angle of the legs. A comparison is then made between the heat sink demands of the hybrid TE design and a conventional bulk TE device where it is found that the lower cooling power density of the hybrid TE results in a reduction of heat sink demands as compared to bulk TE modules. The modeled performance suggest that the hybrid TE device may be advantageous in low cooling power density applications over relatively large areas where the low-cost nature of the device is maximized and less elaborate heat sink designs work effectively, cumulatively improving cost competitiveness.